Evaluating High-Throughput Sequencing Data of Microalgae Living in Melting Snow: Improvements and Limitations1 - Lutz, Stefanie; Procházková, Lenka; Benning, Liane G; Nedbalová, Linda; Remias, Daniel (Fottea (Praha), 2019)
Melting snow fields are an extremophilic habitat dominated by closely related Chlamydomonadaceae (Chlorophyta). Microscopy-based classification of these cryophilic microalgae is challenging and may not reveal the true diversity. High-throughput sequencing (HTS) allows for a more comprehensive evaluation of the community. However, HTS approaches have been rarely used in such ecosystems and the output of their application has not been evaluated. Furthermore, there is no consensus on the choice for a suitable DNA marker or data processing workflow. We found that the correct placement of taxonomic strings onto OTUs strongly depends on the quality of the reference databases. We improved the assignments of the HST data by generating additional reference sequences of the locally abundant taxa, guided by light microscopy. Furthermore, a manual inspection of all automated OTU assignments, oligotyping of the most abundant 18S OTUs, as well as ITS2 secondary structure analyses were necessary for accurate species assignments. Moreover, the sole use of one marker can cause misleading results, either because of insufficient variability within the locus (18S) or the scarcity of reference sequences (ITS2). Our evaluation reveals that HTS output needs to be thoroughly checked when the studied habitats or organisms are poorly represented in publicly available databases. We recommend an optimized workflow for an improved biodiversity evaluation of not only snow algal communities, but generally 'exotic' ecosystems where similar problems arise. A consistent sampling strategy, two- molecular marker approach, light microscopy-based guidance, generation of appropriate reference sequences and final manual verification of all taxonomic assignments are highly recommended.
Keywords: oligotyping; red snow; high-throughput sequencing; 18S rDNA; ITS2 rDNA; Illumina; secondary structure; Sanger; OTU clustering; snow algae